The coming of the Greeks : Indo-European conquests in the Aegean and the Near East - Drews, Robert (Princeton University Press, 1988)
When did the Indo-Europeans enter the lands that they occupied during historical times? And, more specifically, when did the Greeks come to Greece? Robert Drews brings together the evidence, historical, linguistic, and archaeological, to tackle these important questions.